THE POTENTIAL VALUE OF ULTRASOUND IN DIAGNOSIS OF SOFT TISSUE SARCOMA (LITERATURE REVIEW) - I. G. Frolova; O. V. Kotova; Yu. I. Tyukalov; S. A. Velichko; E. Е. Bober; Zh. A. Startseva; A. I. Konovalov; А. V. Bogoutdinova (Сибирский онкологический журнал)
Literature data on the potential value of ultrasound imaging in diagnosis of soft tissue sarcoma were analyzed. Ultrasound in B-regime was used to assess the extent of soft tissue sarcoma, Doppler ultrasonography was used to study tumor vascularization and sonoelastography was useful to differentiate benign from malignant tumors of soft tissues. The analysis of diagnostic value of ultrasound in detection of soft tissue lesions was carried out.  Criteria characterizing various histological types of tumors were identified.